PENCATATAN PERKAWINAN BEDA AGAMA DI PN YOGYAKARTA PERSPEKTIF MAQASHID ASY-SYARI’AH - Mamira, Adelia; Ibrahim, Malik (LPPM Universitas Bina Bangsa, 2023)
Interfaith marriages in Yogyakarta got opportunities since the issuance stipulation number 378/PDT.P/2022/PN YYK by the Yogyakarta District Court. The stipulation contains the granting of the registration of interfaith marriages. As a result, other interfaith couples started making the same request in the following months. It is undeniable that the phenomenon of interfaith marriage cannot be denied from the heterogeneous life of society in Indonesia. This article examines the Yogyakarta District Court's decision on interfaith marriage from the perspective of Maqāsid asy-syarī'ah. By using the perspective of Maqāsid asy-syarī'ah we will be able to examine the philosophical foundations for the basic purposes for which they were enacted, reasons for rationality, 'illat law, legal determination, as well as various other legal applications. The results of the research that can be concluded are that the registration of interfaith marriages in the Yogyakarta District Court results in more harm than benefit. So that it is not in accordance with the ideals of benefit to be achieved in Islam and out of the nature and objectives of Islamic law